Experiences Influencing upon the Significance of Obstetric Care in Mexican Nurses - Consuelo Martínez Villa; Yesica Rangel Flores (Universidad de Antioquia, 2018)
Objective. This work sought to learn which and how are the professional experiences that influence upon significance processes of obstetric care in nurses working in toco-surgery rooms. Methods. This was a qualitative study with grounded theory approach. Individual interviews were conducted with 16 nurses who work in two public hospitals in a border city in northern Mexico. Data analysis was performed according to that proposed by Strauss and Corbin. Results. Four categories were identified that explain the relationship established among the professional experiences and the significance processes of obstetric care; these are: Dilution of borders and demand for interculturality, Modification in the scale of values associated to care, Institutional and public policy crises, and Violence endured within the work setting. Obstetric care is signified within an imaginary that recognizes the existence of a globalized context, which requests problematizing the worldview not of the "other" but of "many others", and not merely from those receiving care, but also from other professionals who participate in institutional care. Conclusion. Significance processes analyzed show how the socio-historical situation and current policy require new attitudinal skills and knowledge for nursing to participate efficiently in obstetric care.   How to cite this article: Martínez C, Rangel Y. Experiences Influencing upon the Significance of Obstetric Care in Mexican Nurses. Invest.  Educ. Enferm. 2018; 36(1):e12.